Utilization of AI-Based Microsoft Edge Pdf Reader as a Support Medium for Digital Literacy and Research for Arabic Education Students - Siregar, Ali Andra Prasetyo; Novian, Zailani; Pradana, Muhammad Rif’an Alfaudin Adi; Maryamah, Lu’lu’atul; Novita, Nanda (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The massive integration of Artificial Intelligence (AI) in higher education has transformed how students The massive integration of Artificial Intelligence in higher education has radically changed the way students process knowledge and conduct academic research. This phenomenon requires digital literacy adaptation, especially for students who encounter scientific texts with high linguistic complexity. Purpose and Scope: This study aims to analyze the use of AI-based features in Microsoft Edge Pdf Reader specifically Copilot and Integrated Translator as a medium to support digital literacy and research efficiency for Arabic Language Education students. Method: This study uses a descriptive qualitative approach with an auto-ethnographic technical case study design, in which the researcher's personal practices are positioned as the main instrument. Data were collected through the documentation of digital artifacts in the form of screenshots that recorded dialogical and operational interactions with intelligent assistants. Summary of Results and Conclusions: Findings show that AI transforms static documents into interactive dialogic texts that enable analytical engagement beyond linear reading. Copilot proved effective in accelerating the extraction of key ideas from academic texts, while the integrated translation feature significantly reduced language barriers in Arabic and English primary references. This human-AI interaction enhances intellectual depth through the concept of Explainable Artificial Intelligence (XAI), which ensures system transparency. Scientific Contributions and Recommendations: This research provides practical contributions to the development of a technology-responsive Arabic Language Education curriculum to create an efficient research ecosystem that upholds human values and scientific accountability. For future research, it is recommended to explore the long-term impact of AI use on student idea originality and its effectiveness on various other digital learning platforms.